Thoracoscopic biopsy in the diagnosis of lung and pleural diseases - Kharel, Ashish; Thakur, Binay; Yang, Ming; Bhandari, Nikesh; Sun, Zhenqing; Shrestha, Shashank; Ghimire, Bhuwan; Neupane, Deewas (Nepalese Journal of Cancer, 2023)
Background: Thoracoscopy is a useful procedure for evaluation and diagnosis of pleural effusion and other thoracic disorders. Our study aimed to evaluate the scope and use of thoracoscopic biopsy for the evaluation of thoracic disorders and report on the outcomes of this technique.Methods: Patients undergoing thoracoscopic biopsy procedure from March 2022 to May 2023 were analyzed for indications, complication and outcomes.Results: 85 patients underwent thoracoscopic biopsy over a period of 15 months, of which 38 (44.7%) were males and 47 (55.3%) were females. The mean age was 60 years. Cough, dyspnea and chest pain were the most common presenting symptoms. Thoracosopy was most commonly done on the right side (67.1%). Pleura (57.6%) was the most common biopsy site, followed by lungs (22.4%), lymph node (12.9%) and mediastinum (3.7%). One case was converted to open procedure. Post operative complication rate was 3.5%. Adenocarcinoma (31.8%) was the most common histology, followed by squamous cell carcinoma (9.4%). 36.5% patients had benign disease and 11.8% patients had metastatic extra-thoracic malignancy.Conclusion: Thoracoscopy is a safe and simple procedure for diagnosis of pleural and other thoracic disorders with the advantage of tissue sampling from lesion under direct visualization. It is a useful tool in the armamentarium of thoracic surgeons.